Pemantauan Jaringan Menggunakan Aplikasi The Dude - Reski Lasari; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Network monitoring is an important activity carried out in monitoring any changes that occur, determine whether each device is connected to the network. The risk of damage and network disruption increases, the network admin must always monitor the entire network system in real time. Monitoring system assist the admin in monitoring the network system that are installed. The Dude also allows for monitoring services that run on each network host, and give a warning on any status changes. As changes the device from UP to Down or Down to Up, that notifications via telegram. The application is used to monitor the network, the notification system will provide the latest information about the condition of the device that has been detected and read The Dude Application that has been set and installed in the Bung Application through the Telegram Application. Test show that all devices connected the network have been detected and read application The Dude, the device is dead, damaged and disconnected, the connection is marked by ping that experience time-out then the device will go down, in that condition the notification will send messages automatically the admin via Telegram media that contains information about the condition the device. The notification system the form of Telegram the admin to know the condition the device without having to see it in real time so as to provide work effectiv for the admin. Keywords : Monitoring, Notification, The Dude Application, Telegram Application.